Pacifist Prophet : Papunhank and the Quest for Peace in Early America - Pointer, Richard W., 1955- (Book collections on Project MUSE., 2020)
"Pacifist Prophet recounts the untold history of peaceable Native Americans in the eighteenth-century, as explored through the world of Papunhank (c1705-1775), a Munsee prophet, preacher, reformer, and diplomat. Papunhank's life was dominated by a search for a peaceful homeland in Pennsylvania and the Ohio country amid the upheavals of the era from the Seven Years' War to the American Revolution."--